Contentious Belonging : The Place of Minorities in Indonesia - Ricci, Ronit; Fealy, Greg, 1957- (Indonesia update series., 2019)
Contention has surrounded the status of minorities throughout Indonesian history. Two broad polarities are evident: one inclusive of minorities, regarding them as part of the nation's rich complexity and a manifestation of its "Unity in Diversity" motto; the other exclusive, viewing with suspicion or disdain those communities or groups that differ from the perceived majority. State and community attitudes towards minorities have fluctuated over time. Some periods have been notable for the acceptance of minorities and protection of their rights, while others have been marked by anti-minority discrimination, marginalisation and sometimes violence. This book explores the complex historical and contemporary dimensions of Indonesia's religious, ethnic, LGBT and disability minorities from a range of perspectives, including historical, legal, political, cultural, discursive and social. It addresses fundamental questions about Indonesia's tolerance and acceptance of difference, and examines the extent to which diversity is embraced or suppressed.